2014
DOI: 10.4172/2167-0919.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunication System Based on Fuzzy Graphs

Abstract: Telecommunication is one of the unavoidable utilities of daily life. Telecommunication service providers have data records of its users. These records are represented by crisp graphs. Certain parameters like center persons, churn prediction, etc. are more perfectly calculated if the data are represented by fuzzy graphs. In this paper, we have introduced a fuzzy telecommunication network (FTN) using fuzzy graph theory.Star persons and related terms are defined in this fuzzy telecommunication network.A small exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Samanta and Pal in [20] suggested that a social network can be represented by a fuzzy graph, there by introducing the concept of fuzzy social network. A telecommunication network is a social network and the same authors in [21] discussed telecommunication network by using a fuzzy graph model. In this section, a method to represent the land line telecommunication network (LTN) by an undirected fuzzy graph is proposed by modifying the membership values of the links in the telecommunication network suggested by Samanta and Pal in [21].…”
Section: Representation Of Land Line Telecommunication System By a Fuzzy Graph Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Samanta and Pal in [20] suggested that a social network can be represented by a fuzzy graph, there by introducing the concept of fuzzy social network. A telecommunication network is a social network and the same authors in [21] discussed telecommunication network by using a fuzzy graph model. In this section, a method to represent the land line telecommunication network (LTN) by an undirected fuzzy graph is proposed by modifying the membership values of the links in the telecommunication network suggested by Samanta and Pal in [21].…”
Section: Representation Of Land Line Telecommunication System By a Fuzzy Graph Modelmentioning
confidence: 99%
“…A telecommunication network is a social network and the same authors in [21] discussed telecommunication network by using a fuzzy graph model. In this section, a method to represent the land line telecommunication network (LTN) by an undirected fuzzy graph is proposed by modifying the membership values of the links in the telecommunication network suggested by Samanta and Pal in [21]. The modifications include representation of telecommunication system by an undirected fuzzy graph G:(V, σ , µ) instead of the directed fuzzy graph G → (V, σ , μ → ) where the membership value μ → (a, b) of the link between two customers a and b depends on t, the outgoing call time of a to b, whereas in G, the membership value µ(a, b) depends on the variable t , the sum of out-going call durations of a to b and of b to a.…”
Section: Representation Of Land Line Telecommunication System By a Fuzzy Graph Modelmentioning
confidence: 99%
See 3 more Smart Citations